Does Post-Transplant Cytomegalovirus Increase the Risk of Invasive Aspergillosis in Solid Organ Transplant Recipients? A Systematic Review and Meta-Analysis - Nipat Chuleerarux; Achitpol Thongkam; Kasama Manothummetha; Saman Nematollahi; Veronica Dioverti-Prono; Pattama Torvorapanit; Nattapong Langsiri; Navaporn Worasilchai; Rongpong Plongla; Ariya Chindamporn; Anawin Sanguankeo; Nitipong Permpalung (Journal of Fungi, 2021)
Background: Cytomegalovirus (CMV) and invasive aspergillosis (IA) cause high morbidity and mortality in solid organ transplant (SOT) recipients. There are conflicting data with respect to the impact of CMV on IA development in SOT recipients. Methods: A literature search was conducted from existence through to 2 April 2021 using MEDLINE, Embase, and ISI Web of Science databases. This review contained observational studies including cross-sectional, prospective cohort, retrospective cohort, and case-control studies that reported SOT recipients with post-transplant CMV (exposure) and without post-transplant CMV (non-exposure) who developed or did not develop subsequent IA. A random-effects model was used to calculate the pooled effect estimate. Results: A total of 16 studies were included for systematic review and meta-analysis. There were 5437 SOT patients included in the study, with 449 SOT recipients developing post-transplant IA. Post-transplant CMV significantly increased the risk of subsequent IA with pORs of 3.31 (2.34, 4.69), I2 = 30%. Subgroup analyses showed that CMV increased the risk of IA development regardless of the study period (before and after 2003), types of organ transplantation (intra-thoracic and intra-abdominal transplantation), and timing after transplant (early vs. late IA development). Further analyses by CMV definitions showed CMV disease/syndrome increased the risk of IA development, but asymptomatic CMV viremia/infection did not increase the risk of IA. Conclusions: Post-transplant CMV, particularly CMV disease/syndrome, significantly increased the risks of IA, which highlights the importance of CMV prevention strategies in SOT recipients. Further studies are needed to understand the impact of programmatic fungal surveillance or antifungal prophylaxis to prevent this fungal-after-viral phenomenon.